The Use of Smart Speakers in Disability: A Scoping Review - Rafael Tavares (2021)
Introduction: Smart speakers, like Amazon Echo and Google Nest, are established in the worldwide mainstream market, being available to the general population. The artificial intelligence programmed within these conversational devices and their compatibility with different networks creates opportunities for a wide range of interventions in different populations with disability, in a smart home context; Goals: To understand how smart speakers are being used by individuals with disability, uncovering possibilities of intervention and considering their potential; Methods: A scoping review of articles present in PubMed/Medline, B-On, Scopus and Web of Science databases in February 2021 was conducted. Articles published since 2016 until 2021, written in Portuguese and English and peer reviewed were considered. Studies exploring the use of general market available smart speakers (Google Nest / Home, Amazon Echo, Invoke, HomePod) as an home intervention agent or environmental control unit, focusing on individuals with sensorial, cognitive, emotional and motor impairment were included; Results: Different approaches and user demands were identified. Devices were applied as a single solution or as an element of bigger systems, interacting with other devices or software’s; Conclusions: The identification of different interventions for different disabilities underlines the intervention potential of these devices with observed functional improvements in physical, cognitive, sensory, and emotional disabilities. These improvements can promote the replacement of expensive devices created for niche populations and closed systems developed with specific goals in a specific form of disability. As customization is a relevant feature, the application of SS does not dispense with technical support in the process.